Comparison of CISNE and MASCC Score in Predicting Complications on Post Chemotherapy Febrile Neutropenia - Sharifah Shakinah; Erni Juwita Nelwan; Anna Mira Lubis; Robert Sinto; Khie Chen Lie (Acta Medica Indonesiana, 2024)
Background: Febrile neutropenia (FN) is an oncologic emergency which commonly occurrs in patients who undergo chemotherapy, with a mortality rate of 12.5%. Risk stratification in FN plays an important role in increasing the accuracy of therapy. This study aims to compare the performance between CISNE score and MASCC score in predicting complications on post-chemotherapy FN in solid and hematologic malignancy.  Methods: This is a retrospective cohort study on FN patients undergoing inpatient treatment at Cipto Mangunkusumo Hospital between July 2015 and December 2019. Basic demographic and clinical data were collected from medical records. Subjects were grouped based on the CISNE and MASCC score, and complications during hospitalization were recorded. Predictive performance of each score was analyzed and compared using area of under curve.  Results: CISNE score showed a better performance both in solid malignancy with AUC of CISNE score (0.80 CI 95% 0.73-0.88, p = 0.00) compared to AUC of MASCC score (0.68; 95% CI 0.59 – 0,78, p = 0.00) and in hematologic malignancy with AUC of CISNE score (0.85; 95% CI 0.77 - 0.93, p = 0.00) and AUC MASCC score (0.65 ; 95% CI 0.54 - 0.76, p = 0.007). Conclusion: CISNE score showed a better performance compared to MASCC score in predicting in-hospital complication in both solid and hematologic malignancy with cut-off point of 2.